2008
DOI: 10.1021/bm801160s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Protein−Protein Complex Coacervation and Biphasic Release of Salbutamol Sulfate from Coacervate Matrix

Abstract: Turbidimetric titration was used to initiate associative intermolecular interactions between a pair of protein molecules, gelatin-A and gelatin-B, having complementary charges that led to pH-induced liquid-liquid phase separation and the formation of complex coacervate. The stoichiometric binding ratio was found to be [gelatin-A]/[gelatin-B]=3:2. The size of soluble intermolecular aggregates present in the supernatant exhibited interesting time-dependent coacervation because of residual electrostatic interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…Tiwari et al, examined both the encapsulation and release of salbutamol sulfate, a bronchodilator used in the treatment of asthma and other chronic airway diseases, from coacervates formed from a pair of protein molecules, gelatin-A and gelatin-B [141]. Linear viscoelastic characterization showed that drug encapsulation caused a significant decrease in the storage modulus (G'), suggesting that the coacervate matrix was disturbed and weakened by the presence of the drug, and a slight increase in the loss modulus (G"), suggesting a commensurate fluidization of the material.…”
Section: Encapsulation and Releasementioning
confidence: 99%
“…Tiwari et al, examined both the encapsulation and release of salbutamol sulfate, a bronchodilator used in the treatment of asthma and other chronic airway diseases, from coacervates formed from a pair of protein molecules, gelatin-A and gelatin-B [141]. Linear viscoelastic characterization showed that drug encapsulation caused a significant decrease in the storage modulus (G'), suggesting that the coacervate matrix was disturbed and weakened by the presence of the drug, and a slight increase in the loss modulus (G"), suggesting a commensurate fluidization of the material.…”
Section: Encapsulation and Releasementioning
confidence: 99%
“…Light scattering measurements assigned the following dimensions to the GA chains: R g = 55±5 nm and R h = 58±6 nm. Thus, the chain stiffness determined from the ratio [14] R h /R g was 0.95. This clearly attributes a less flexible chain conformation compared to gelatin-B.…”
Section: Dna-gelatin a / Aqueous Mediummentioning
confidence: 99%
“…Little is known about the affect of ionic strength on such binding mechanisms which is the main focus of this work. In order to get a better feeling of the system, the results are compared with the salient features reported in gelatin simple coacervates [25,62], and gelatin A-gelatin B [14], gelatin-chitosan [11] and gelatin A-agar [63] complex coacervates. The surface selective binding process has been explained through potential energy calculations following a simple model.…”
Section: Surface Patch Bindingmentioning
confidence: 99%
See 2 more Smart Citations